Rhinovirus protease cleavage of nucleoporins: perspective on implications for airway remodeling - Moorhouse, Jennifer; Val, Nicole; Shahriari, Shadi; Nelson, Michelle; Ashby, Regan; Ghildyal, Reena (Frontiers in Microbiology, 2024)
Human Rhinoviruses (RV) are a major cause of common colds and infections in early childhood and can lead to subsequent development of asthma via an as yet unknown mechanism. Asthma is a chronic inflammatory pulmonary disease characterized by significant airway remodeling. A key component of airway remodeling is the transdifferentiation of airway epithelial and fibroblast cells into cells with a more contractile phenotype. Interestingly, transforming growth factor-beta (TGF-), a well characterized inducer of transdifferentiation, is significantly higher in airways of asthmatics compared to non-asthmatics.RV infection induces TGF- signaling, at the same time nucleoporins (Nups), including Nup153, are cleaved by RV proteases disrupting nucleocytoplasmic transport. As Nup153 regulates nuclear export of SMAD2, a key intermediate in the TGF- transdifferentiation pathway, its loss of function would result in nuclear retention of SMAD2 and dysregulated TGF- signaling.We hypothesize that RV infection leads to increased nuclear SMAD2, resulting in sustained TGF- induced gene expression, priming the airway for subsequent development of asthma. Our hypothesis brings together disparate studies on RV, asthma and Nup153 with the aim to prompt new research into the role of RV infection in development of asthma.